A review of current performance of rare earth metal-doped barium zirconate perovskite: The promising electrode and electrolyte material for the protonic ceramic fuel cells. (September 2021) - Rasaki, Sefiu Abolaji; Liu, Changyong; Lao, Changshi; Chen, Zhangwei
Abstract: Rare-earth metal doped barium zirconate (RE + -BaZrO3 ) materials are ionic and electronic conductors currently showing double functions in the protonic ceramic fuel cells (PCFCs). Specifically, RE + -BaZrO3 are relevant as electrode and electrolyte for PCFCs. They have appreciable electron-ionic conductivity (e − /H + /O 2− ) at moderate temperature (≥500 °C) making them a better choice when compared to other perovskites. However, in these materials (RE + -BaZrO3 ), challenges such as weak proton uptake and insufficient catalytic sites still exist and need to be addressed. From physic-chemical perspectives, improvement can be made possible through deeper understanding of proton uptake mechanism and catalytic sites resulting from structure engineering. Based on that, this review focuses on importance of synthesis application for tuning the structural properties of RE + -BaZrO3 materials, and hence enhances their current performances. The current advances made through material modification are discussed too. The main emphasis and discussions are on RE + -BaZrO3 material design as electrode and electrolyte for PCFCs. The reaction mechanisms associated with the material proton uptakes are explicitly discussed. Putting all relevant analytical results into consideration, the primary approaches to improve the performance of the electrode and electrolyte-based on RE + -BaZrO3 materials are indicated. Graphical abstract: Image 1